Improving health care encounters and communication with transgender patients. (March 2014) - Redfern, Jan S.; Sinclair, Bill
<x content-type="archive" xml:space="preserve">Abstract</x> Background/objectives Transgender persons represent a generally ill-served or underserved population. This marginalized group continues to experience considerable difficulty in obtaining culturally competent health care despite recommendations by professional organizations and introduction of antidiscrimination legislation. This review examines communication and procedural barriers to transgender health care and suggests practical steps to help ameliorate disparities and unequal treatment. Methods Publications addressing health disparities and communication and procedural barriers to health care of transgender persons were identified by a structured search of electronic databases. The most pertinent articles are reviewed and consolidated with the authors' collective experiences. Results To improve their interactions and communication with transgender persons, health care providers can take a variety of practical steps in several key areas: office environment, registration forms, initial interview and assessment, confidentiality, personnel training, awareness of and compliance with applicable antidiscrimination legislation, health insurance-related issues, and outreach and transgender health promotion. Conclusions Enhancing patient satisfaction through culturally competent health care, quality assurance, and patient feedback is critical to creating open lines of communication between practitioner and patient and fostering a favorable context for transgender patient care.